2021
DOI: 10.1002/pon.5683
|View full text |Cite
|
Sign up to set email alerts
|

Reducing distress and depression in cancer patients during survivorship

Abstract: Objective Distress and depression are prevalent in cancer patients throughout survivorship and are associated with adverse outcomes. This study examines the association between outpatient psycho‐oncology treatment and distress and depression in cancer patients. Methods This is a prospective observational study of adult patients with a primary diagnosis of cancer referred for psycho‐oncology services. Patients were seen for two psycho‐oncology visits in a single clinical setting with various qualified providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(66 reference statements)
0
3
0
1
Order By: Relevance
“…Cancer is one example of a disease that is often accompanied by distress. Yet studies have shown that, for instance, few patients experiencing mental health issues such as depression or anxiety occurring while undergoing cancer treatment reported these concerns to physicians nor were physicians likely to recognize and then refer these patients for psychological treatment, and most of those identified by nurses as needing psychological treatment were referred for, but did not receive, treatment (Maguire, 1985; Ryan et al, 2005), perhaps because depression and anxiety can mimic physical symptoms of cancer as well as other diseases (Molinaro et al, 2021; Ryan et al, 2005). Other studies have looked across medical conditions to learn more about whether medical patients disclose, or want to disclose, psychological concerns and whether medical providers recognize cues of psychological distress in their patients.…”
Section: Disclosure About Phimentioning
confidence: 99%
“…Cancer is one example of a disease that is often accompanied by distress. Yet studies have shown that, for instance, few patients experiencing mental health issues such as depression or anxiety occurring while undergoing cancer treatment reported these concerns to physicians nor were physicians likely to recognize and then refer these patients for psychological treatment, and most of those identified by nurses as needing psychological treatment were referred for, but did not receive, treatment (Maguire, 1985; Ryan et al, 2005), perhaps because depression and anxiety can mimic physical symptoms of cancer as well as other diseases (Molinaro et al, 2021; Ryan et al, 2005). Other studies have looked across medical conditions to learn more about whether medical patients disclose, or want to disclose, psychological concerns and whether medical providers recognize cues of psychological distress in their patients.…”
Section: Disclosure About Phimentioning
confidence: 99%
“…Following a cancer diagnosis, just nine participants (15%) expected to receive counselling (psychosocial support) from their care providers, while one-third of the participants were resigned and had no further expectations. It is well recognized in the literature on psycho-oncology that psychological interventions, not only at the time of a cancer diagnosis but throughout survivorship, can improve outcomes [ 27 ]. It is well known that several gaps exist in primary health care and health systems in the Latin American and Caribbean region, adversely affecting the quality of care [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advice on strategies to manage stress was informally given by physicians in an unstructured manner, dependent on the treating physician and patient relationship. Molinaro et al purport the impact of psycho-oncology in reducing distress and depression in cancer patients [ 27 ]. Techniques such as relaxation and meditation, as well as, physical and recreational activities were discovered by participants for stress management.…”
Section: Discussionmentioning
confidence: 99%
“…A assistência de saúde mental a pacientes diagnosticados com câncer deve ser prioridade no tratamento multiprofissional, pois o recebimento do diagnóstico pelo paciente pode desencadear a presença do transtorno depressivo tanto por uma reação de ajustamento quanto por uma resposta biopsicossocial e a detecção do sofrimento psicológico é importante para o tratamento da saúde mental centrado no paciente. (MOLINARO, J. et al, 2021). Dessa maneira, esta revisão integrativa da literatura buscou analisar e compreender de que maneira o cotidiano de pacientes oncológicos é impactado pela depressão.…”
Section: Introductionunclassified